Distribution of human papillomavirus (HPV) genotypes and bacterial vaginosis presence in cervical samples from Paraguayan indigenous. (October 2015) - Mongelos, Pamela; Mendoza, Laura Patricia; Rodriguez-Riveros, Isabel; Castro, Amalia; Gimenez, Graciela; Araujo, Patricia; Paez, Malvina; Castro, Wilberto; Basiletti, Jorge; González, Joaquín; Echagüe, Gloria; Diaz, Valentina; et al.
Highlights: HPV genotypes were detected and showed a slightly different pattern from previous local studies. This work confirms the high prevalence of HR-HPV infection in women with normal cytological results. There was observed an association between BV and HR-HPV, Chlamydia trachomatis, Trichomonas vaginalis, Mycoplasma hominis . This information could be used by national health authorities for the improvement of prevention programs. The study had the additional social value of permitting gynecological screening access and health care education to many indigenous women. Summary: Objective: To determine the frequency of human papillomavirus (HPV) types and to assess bacterial vaginosis (BV) possible associations with cervical infections in indigenous Paraguayan women of the Department of Presidente Hayes. Methods: This study included 181 sexually active women without cervical lesions. HPV typing was performed by polymerase chain reaction with primers PGMY 09/11 followed by reverse line hybridization. BV was diagnosed by the Nugent criteria using the results from a Gram stain smear. Results: Sixteen percent of women were positive for at least one high risk HPV type (HR-HPV). The most frequent genotypes were HPV 16 (4.4%), followed by HPV 58 (3.3%), HPV 45 (3.3%), HPV 53 (2.8%) and HPV 11 (2.8%). A significant association between HR-HPV and BV was observed (p=0.01). In addition, women with BV had a higher frequency of Chlamydia trachomatis (p=0.0007), Trichomonas vaginalis (p=0.00009), Mycoplasma hominis (p=0.001) . Conclusions: A large variety of HPV genotypes was detected and showed a slightly different pattern from previous studies on urban women in Paraguay, with the predominance of HR-HPV. Furthermore, the information of co-infections involved in BV could be useful for the improvement of national prevention programs, as well as for laboratory surveillance of these genital infections.